Targeting survivin in leukemia - Bing Z. Carter; Michael Andreeff (Frontiers Media S.A., 2011)
Survivin, a member of the inhibitors of apoptosis family of proteins, is one of the most frequently upregulated transcripts in solid tumors and hematopoietic malignancies. Survivin's importance in tumorigenesis is attributed to the fact that it has two functions: to suppress apoptosis and to regulate cell division. The combination of these two functions gives a significant growth and survival advantage on neoplastic cells. This, together with its overexpression in cancer cells, its association with resistance to chemo- and other therapies, and the resulting poor prognosis observed in certain tumors makes survivin a promising target for therapy. In this review, we describe what is currently know about survivin regulation in normal and malignant cells, focusing in particular on the aberrant expression of the protein in leukemia and its possible clinical implications. Various strategies to target survivin will also be described.